Hambatan Dalam Melakukan Pembuktian Terhadap Tindakan Money Politic Pada Masa Kampanye 2024 - Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Anan, Muhammad Jafar; Ulfa, Aulia; Afifah, Alya; Samosir, Fransiska Hirim M. (Innovative: Journal Of Social Science Research, 2024)
The purpose of this research is to identify the various obstacles that may arise in the process of proving money politics cases during the 2024 general election campaign. This research will use a case study of the General Election Supervisory Agency (Bawaslu) to gain a deeper understanding of the forms of obstacles that may be faced in uncovering money politics practices. By understanding these barriers, it is hoped that effective strategies can be developed to prevent and handle money politics cases in the future. The research method used in this research is descriptive qualitative with the research subjects are members of Bawaslu. The data collection technique used is qualitative and the data analysis techniques used in this research are interview techniques and narrative techniques. The results showed that proving the act of money politics during the campaign period has significant challenges. Factors such as public ignorance, witness courage to report, and limited resources are the main obstacles in uncovering and proving money politics practices. In addition, interference from interested parties and threats to the integrity of the investigation also complicate the evidentiary process.